Relative Effectiveness of Acceptance/Commitment and Schema Therapies on Love Trauma Syndrome and Self-compassion in Unmarried Girls With Emotional Breakdown - Rohollah Sharifi Nejad Rodani; Fatemeh Sadat Marashian; Masoud Shahbazi (Journal of Research & Health, 2023)
Background: Failure to establish and maintain close romantic relationships with commitment can hinder an individual’s development and impose adverse effects on their well-being in life due to the potential emergence of serious problems. The present study investigates the relative effectiveness of acceptance and commitment therapy (ACT) and schema therapy on love trauma syndrome and self-compassion in unmarried girls with emotional breakdowns. Methods: The statistical population of this study included all unmarried girls with emotional breakdowns who visited counseling centers in Ahvaz, Khuzestan Province, Iran, in 2022. The convenience sampling method was employed to select 45 individuals randomly assigned to two experimental groups and one control group (n=15 per group). This quasi-experimental research adopted a pre-test-post-test design with a control group design and follow-up. The love trauma inventory and the self-compassion scale–short form were used to collect the data. The analysis of covariance was used for data analysis in the SPSS software, version 26. Results: The results indicated that ACT and schema therapy significantly affected the love trauma syndrome and self-compassion in unmarried girls with emotional breakdowns (P<0.001). Moreover, schema therapy had more significant effects than ACT on the participants’ love trauma syndrome and self-compassion (P<0.001). The results also demonstrated that the effectiveness of act and schema therapy on self-compassion and love trauma syndrome continued until the follow-up phase. Conclusion: Schema therapy is a more appropriate method for addressing the love trauma syndrome and self-compassion in unmarried girls with emotional breakdowns. Based on these results and considering the role of schema therapy, it is possible to help women with emotional breakdowns to enjoy self-compassion and reduce their love trauma syndrome by holding schema therapy sessions.